Sources and exchanges of mercury in the waters of the Northwestern Mediterranean margin. (April 2018) - Cossa, Daniel; Durrieu de Madron, Xavier; Schäfer, Jörg; Guédron, Stéphane; Marusczak, Nicolas; Castelle, Sabine; Naudin, Jean-Jacques
Highlights: Distribution and fluxes of total Hg have been examined in the waters of the NW Mediterranean. Concentrations varied from 0.6 to 4.57 pmol L −1 on the inner shelf, and from 0.5 to 1.5 pmol L −1 at open sea. The major Hg input to the Gulf of Lions is from the open sea. In the open sea, Hg and dissolved oxygen distributions are inverse. Abstract: Ocean margins are focal regions in terms of mercury (Hg) exchanges between the continent and the open sea. The aim of this paper is to describe the distribution and partition of Hg between the gaseous, dissolved and particulate phases in the waters of the Northwestern Mediterranean (NWM) margin, in order to assess the Hg sources and exchanges within the continuum between the continental shelf (Gulf of Lions) and the open sea (Northern Gyre). Mean (±standard deviation) of total Hg species (HgT) concentrations in unfiltered water samples were 1.52 ± 1.00 pmol L −1 (n = 36) in the inner shelf, 1.09 ± 0.15 pmol L −1 (n = 30) along the slope, and 1.10 ± 0.13 pmol L −1 (n = 99) in the Northern Gyre. The dissolved phase (<0.45 µm) average concentrations were 0.80 ± 0.47 pmol L −1 (n = 37) in the inner shelf, 0.93 ± 0.20 pmol L −1 (n = 4) along the slope and 0.84 ± 0.10 (n = 20) pmol L −1 in the Northern Gyre. The particulate fraction of Hg decreased very strongly seaward from around 60% on the shelf to 10–25% above the Northern Gyre. Very low dissolved HgT concentrations occurred in the inner shelf water, consistent with the results of incubation experiments, which demonstrated that shelf water is very efficient in both production and release of dissolved gaseous Hg into the atmosphere. In the North Gyre waters column HgT presents a distribution pattern inverse to that of dissolved oxygen, and a slight Hg enrichment in the deep layer (Western Mediterranean Deep Water). The Hg from the open sea water is the largest Hg input to the Gulf of Lions (∼5.7 kmol yr −1 ), whereas inputs from the riverine source account for ∼3.4 kmol yr −1 and atmospheric deposition for less than 0.5 kmol yr −1 . The Hg accumulated in the sediments of the shelf is ∼4.5 kmol yr −1, including 0.6–1.7 kmol yr −1 in the Rhône prodelta sediments. The evasion to the atmosphere represents a Hg flux of ∼2.6 kmol yr −1 .